21 A comparison of coronary haemodynamics in 40cc versus 50cc intra-aortic balloon pumps. (5th June 2017) - Briceno, Natalia; Silva, Kalpa De; Lumley, Matthew; Kailey, Balrik; Ellis, Howard; Redwood, Simon; Perera, Divaka
Abstract : Introduction: Randomised trials have questioned the benefit of intra-aortic balloon pump (IABP) counterpulsation in high-risk PCI and shock. A larger capacity balloon has been introduced into routine clinical practice that has been shown to provide greater systolic unloading and diastolic augmentation compared with the standard balloon. Our aim was to investigate whether larger capacity balloons provide a greater augmentation in coronary flow compared with standard capacity balloons. Methods: Seven patients with severe ischaemic cardiomyopathy were studied using a two-treatment, single sequence crossover protocol at the time of elective percutaneous coronary intervention (PCI). Simultaneous coronary pressure and Doppler measurements were undertaken in the target vessel after PCI using a Volcano Combowire, during unassisted and assisted IABP conditions, first with a 40cc IABP and then, five minutes later, with a 50cc IABP. Measurements were taken with intact autoregulation and with autoregulation temporarily disabled by administration of intracoronary adenosine. Coronary wave intensity analysis was performed to characterise the wave energies associated with balloon counterpulsation. Data are presented as mean ± SD. Results: Patients were 65 (±12) years old (75% male). Left ventricular ejection fraction was 29% (±11%) with a coronary jeopardy score of 11 (±2) (maximum possible score=12). There was no difference between the 40cc and 50cc IABP balloons in average peak velocity (50.3±33.6 vs. 49.7±24.2 cm s −1 p=0.916), mean distal coronary pressure (83.4±16 vs. 85.2±20 mmHg, p=0.549) (see Figure 1), or microvascular resistance (181.6±52.9 vs. 207.5±83.4 mmHgcm −1 s, p=0.218) when autoregulation was disabled. Results were similar during basal assisted conditions. On wave intensity analysis, a late diastolic forward compression wave was identified during IABP support that was not seen during unassisted conditions. The magnitude of the IABP-forward compression wave was numerically greater with the 50cc balloon during basal conditions, which did not reach statistical significance (1.7±1.7 vs. 2.8±3.1, W m −2 s −2 × 10 5, p=0.155) (see Figure 2). Conclusions: The larger capacity balloon does not provide greater augmentation in coronary flow or reduction in microvascular resistance compared with the standard balloon during basal or hyperaemic conditions. We did not measure left ventricular afterload or myocardial oxygen demand in this study and cannot exclude a differential effect of the 50cc balloon on myocardial oxygen supply and demand.